Toxicity of Triazavirin, a Novel Russian Antiinfluenza Chemotherapeutic - S. YA. Loginova; S. V. Borisevich; V. L. Rusinov; U. N. Ulomsky; V. N. Charushin; O. N. Chupakhin (Антибиотики и Химиотерапия)
The study of the toxicity of triazavirin, a new antiinfluenza agent, showed that the maximum concentration of the drug, inducing no microscopically visible changes in the structure of the monolayer and the cells of the MDCK and SKEV cell cultures, was 128 and 100 mcg/ml respectively. The maximum drug dose for single intraperitoneal administration inducing no signs of acute intoxication in albino mice weighing 10-12 g was 1000 mg/kg. In investigation of the chronic toxicity it was shown that oral administration of the drug (by 0.05 ml) to the albino mice in a dose of 200 mg/kg (maximum possible concentration by the solubility) daily for 10 days was well tolerated by the laboratory animals. The maximum tolerable dose of triazavirin for the albino mice was ≥200 mg/kg.